Assessing spatial heterogeneous response of ecosystem service relationships to land use intensification - Mingli Qiu; Dianfeng Liu (Ecological Indicators, 2023)
Sustainable land use should balance the competing needs for development and protection. Land-use intensification facilitates material benefits from ecosystem, while potentially undermining the capacity of regulate the life-support environment and thus altering trade-offs between ecosystem services (ES). However, there remains a limited understanding of how land-use intensity (LUI) affects the spatial heterogeneity of ES relationships. To address this issue, we first propose an ES synergies (ESS) index, to clarify site-specific ES relationships, based on a combination of the production possibility frontier (PPF) and the technique for order preference by similarity to the ideal solution (TOPSIS). Then, we assess the nonlinear impacts of LUI on ESS, using the generalized additive models (GAMs). A case study was conducted in the Three Gorges region of central China, due to the dilemma between intensive development for poverty alleviation and water-soil retention for ecological protection. The results showed that an increase in LUI caused different rates of decline in ESS. Land-use intensification increased resource inputs and anthropogenic disturbances within entire land parcels, thus disrupting the synergistic relationships between several ES. Specifically, the synergies between water retention and carbon sequestration or biodiversity conservation decreased by more than three times as much as those between water retention and food production. Excessive LUI will reduce the provision of carbon sequestration and biodiversity conservation compared to that of food production for the same level of water retention. However, moderate LUI can promote the synergistic provision of multiple services. For example, an LUI threshold of 2.5, which maximized the synergies of water-soil retention with other ES, showed the optimal balance of diverse ecological benefits at the highest level of intensity. Our study is expected to extend existing knowledge on the spatial heterogeneity of ES relationships by considering site-specific land use, and to mitigate the costs of land management due to ES trade-offs.